Numerical methods: BACS 2222 study guide - Khoo, Chin Foon (Prentice Hall, 2005)
The module consist of eleven chapters which are Computer Representation of Numbers, Error, Solution of Nonlinear Equations, Solution of Linear Systems, Interpolation, Curve Fitting, Numerical Differentiation, Numerical Integration, Eigen Values and Eigen Vectors, Solution of Ordinary Differential Equations and Solution of Partial Differential Equations. Virtually every concept in text is illustrated by example. Extra activities and exercises are provided so that students can have their own practice after studying the chapter. Students are also introduced to the computer software package, i.e. MATLAB, so that they could solve the numerical problems easier, faster and effectively.